2021
DOI: 10.1080/10463283.2020.1852699
|View full text |Cite
|
Sign up to set email alerts
|

How can we master the 2020 Coronavirus pandemic? The role of planning at social levels

Abstract: Mastering global challenges such as the 2020 Coronavirus pandemic requires implementing effective responses at various social levels. Leadership teams (governmental, industrial) need to integrate available information to introduce effective regulation and update their decisions as new information becomes available. Groups (families, peers, teams) need to act persistently, even when these actions oppose members' individual short-term interests. Moreover, individuals need to stay calm and act diligently, while d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 162 publications
(196 reference statements)
1
4
0
Order By: Relevance
“…For instance, calls for unity were more effective when they elicited higher threat ratings, as indicated by significant indirect effects of message source on reconciliatory behavior. Although running counter to findings regarding punishment (e.g., McCrea et al., 2022), these observations comport well with motivation science accounts of how individuals and groups attain their goals (DeShon et al., 2004; Thürmer et al., 2021; Wieber et al., 2012). Threat may be conceived of as an indicator of insufficient goal progress, leading to increased goal‐directed effort (Carver & Scheier, 1990; Thürmer, Scheier et al., 2020).…”
Section: Beyond Punishment: Response Target and Valencesupporting
confidence: 65%
“…For instance, calls for unity were more effective when they elicited higher threat ratings, as indicated by significant indirect effects of message source on reconciliatory behavior. Although running counter to findings regarding punishment (e.g., McCrea et al., 2022), these observations comport well with motivation science accounts of how individuals and groups attain their goals (DeShon et al., 2004; Thürmer et al., 2021; Wieber et al., 2012). Threat may be conceived of as an indicator of insufficient goal progress, leading to increased goal‐directed effort (Carver & Scheier, 1990; Thürmer, Scheier et al., 2020).…”
Section: Beyond Punishment: Response Target and Valencesupporting
confidence: 65%
“…Another promising route for governments' interventions could be reducing the effort needed to comply with behavioral restrictions. For instance, it has been suggested that simple action planning (e.g., what to do when feeling bored) could help people navigate the pandemic by supporting them in dealing with the difficulties of compliance (Bieleke et al 2020;Thürmer et al 2021). Our present results suggest that reducing effort has beneficial effects on behavior and simultaneously reduces boredom.…”
Section: Implications For Policy Makers During a Pandemicmentioning
confidence: 53%
“…Consider hand washing: Individuals might believe that hand washing is neither prudent nor morally right (personal norm), but if they believe that other people expect them to wash their hands and would punish them for failing to wash their hands (social norm), they are more likely to wash their hands – at least in the presence of others – despite their unhygienic personal norm. Social norms may even influence behavior in an automatic fashion, unless this influence is overridden by implementation intentions (Thürmer et al, 2020; see also Thürmer et al, 2021). It is crucial for public health to understand how social norms change.…”
Section: The Present Researchmentioning
confidence: 99%